Healthcare professionals' attitudes towards termination of pregnancy at viable stage. (16th August 2020) - Roets, Ellen; Dierickx, Sigrid; Deliens, Luc; Chambaere, Kenneth; Dombrecht, Laure; Roelens, Kristien; Beernaert, Kim
Abstract: Introduction: Upon prenatal diagnosis of congenital malformations, termination of pregnancy (TOP) may be an option, sometimes at a gestational age when the fetus is already viable (late TOP). We aimed to study attitudes towards late TOP of all tertiary healthcare professionals involved in late TOP practice. Material and methods: A mail survey was conducted among all physicians and paramedical professionals involved in late TOP decision‐making in all eight centers with a Neonatal Intensive Care Unit in Flanders, Belgium (N = 117). The questionnaire contained general and case‐based attitude items. Results: Response rate was 79%. Respondents were either physicians (51.1%) or paramedical professionals (49.9%). The composition of professionals involved in late TOP decision‐making was heterogeneous between the eight centers. Late TOP was highly accepted in both lethal fetal conditions (100%) and serious (but not lethal) fetal conditions (95.6%). Where the fetus is healthy, 19.8% of respondents agreed with late TOP for maternal psychological problems and fewer respondents (13.2%) agreed with late TOP in the case of maternal socio‐economic problems ( P  = .002). Physicians more often preferred feticide over neonatal palliative care in the case of non‐lethal fetal conditions compared with paramedical professionals (68.1% vs 53.2%, P  = .013). Almost nine out of ten respondents (89.1%) agreed that in the event of a serious (non‐lethal) neonatal condition, administering drugs with the explicit intention to end neonatal life was acceptable. Behavioral intentions indicate that even in situations with an unclear diagnosis and unpredictable prognosis, 85.6% of professionals would still consider late TOP. Conclusions: Healthcare professionals practicing late TOP in Flanders, Belgium have a high degree of tolerance towards late TOP, irrespective of sociodemographic factors, and are demanding legislative change regarding active life‐ending in the fetal and neonatal periods. Further research should explore the correlation of attitudes to late TOP with actual medical decisions taken in daily clinical practice.